Developing Speaking Skills of ESL Learners in Rural Schools: A Study Based on the Rural Schools at Manipay - Archana, J.; Paranthaman, V. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
This study examines the development of speaking skills among ESL learners in rural schools in Manipay. The primary objectives were to identify the factors influencing the English-speaking skills of secondary-level students (Grades 10 and 11), to explore the challenges faced by English teachers at this level, and to provide a foundation for enhancing students’ oral communication abilities. An experimental study was conducted in three rural government schools in Manipay. The sample comprised three teachers and 45 randomly selected students. Both qualitative and quantitative research methods were employed, with data collected through classroom observations, teacher interviews, pre-tests, post-tests, and structured speaking tests. The data were analyzed using both statistical and graphical techniques, with numerical data subjected to independent sample tests. The findings revealed that students in rural schools encounter numerous difficulties in developing their speaking skills, which stem from both internal and external factors. Although students recognized the value of English, they lacked confidence, felt shy when speaking, and were reluctant to practice with others. Furthermore, the instructional methods employed by English teachers did not provide learners with sufficient exposure to the target language to foster effective oral communication. The study reveals the possible reasons for the limited adoption of communicative teaching practices and offers recommendations for promoting more effective approaches to teaching English as a foreign language in rural school contexts.
Keywords: Speaking skills; Rural schools; Secondary students; Teacher challenges; Language input